2021
DOI: 10.18632/aging.202782
|View full text |Cite
|
Sign up to set email alerts
|

Conditional survival and hazards of death for peripheral T-cell lymphomas

Abstract: Typically, peripheral T-cell lymphoma (PTCLs) prognosis is estimated using overall survival before treatment. However, these estimates cannot show how prognosis evolves with the changing hazard rate over time. Patients (n = 650) with newly diagnosed PTCLs were enrolled retrospectively. After a median follow-up of 5.4 years, angioimmunoblastic T-cell lymphoma, peripheral T-cell lymphoma, not otherwise specified (PTCL, NOS) and NK/T cell lymphoma had initially lower 3-year conditional overall survival (COS3; i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…PTCL is classified into subtypes such as angioimmunoblastic T-cell lymphoma (AITL), ALK-positive anaplastic large-cell lymphoma (ALK+ALCL), ALK-negative anaplastic large-cell lymphoma (ALK-ALCL), peripheral T-cell lymphoma not otherwise specified (PTCL-NOS), and so on ( 1 , 2 ). Most subtypes have a dismal prognosis ( 3 , 4 ). Due to the rarity and heterogeneity of PTCL, there is still no consensus on the best treatment approach.…”
Section: Introductionmentioning
confidence: 99%
“…PTCL is classified into subtypes such as angioimmunoblastic T-cell lymphoma (AITL), ALK-positive anaplastic large-cell lymphoma (ALK+ALCL), ALK-negative anaplastic large-cell lymphoma (ALK-ALCL), peripheral T-cell lymphoma not otherwise specified (PTCL-NOS), and so on ( 1 , 2 ). Most subtypes have a dismal prognosis ( 3 , 4 ). Due to the rarity and heterogeneity of PTCL, there is still no consensus on the best treatment approach.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study involving 650 patients with newly diagnosed ITCLs and a median follow-up of 5.4 years, it was found that ITCL, NOS and other subtypes demonstrated lower 3-year conditional overall survival rates initially, along with higher risks of death (ranging from 26% to 44.3%). Furthermore, among patients who achieved complete remission following initial treatment, the prognosis varied depending on the specific histological subtype, with ITCL, NOS having a negative impact on the outcomes [ 19 ]. Nevertheless, common risk factors associated with survival were identified.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22]24 In our studies, we did not observe consistency in COS 3 and the annual hazard of death in each risk category. The prior report 39 found different risk stratification might have heterogeneous prognosis for specific sub-population of certain types of cancers. Thus, the results for COS 3 based on the CP score and the BCLC system might not be suitable to predict conditional survival or the annual hazard of death.…”
mentioning
confidence: 95%